PERAN PERAWAT KESEHATAN MASYARAKAT PADA LOKASI RESIKO TINGGI PENULARAN PMS/HIV-AIDS DI WILAYAH KABUPATEN BANYUMAS JAWA TENGAH - , Wasis Eko Kurniawan, S.Kep., Ns. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: A nurse is a person who has finished an education in nursing and has a certificate of the education. There are 4 roles of a nurse based on a workshop conducted in January 1993. They are: (1) Role as a service giver, (2) Role as a manager in service in the institution of nursing, (3) Role as a teacher in nursing science, (4) Role as a researcher and developer in nursing science. The role of a nurse in areas with high risk infection of Sexually Transmitted Diseases (STD)/HIV-AIDS are required to have more roles to overcome STD/HIV-AIDS. Objective: To find out the potential role of the community health nurses in areas with high risk infection of the STD/HIV-AIDS in Banyumas Regency. Research Method: This research is an explorative research using descriptive qualitative approach. The subjects of the research were 25 the nurses who were in charge in 5 Community Health Service and high risk infected community. The sampling method used on the high risk infected community was the snowballing sampling. The data were gathered through observation, interview and documentation. The data analysis were conducted through three levels, they were reducing data, displaying data and drawing conclusion/verification. Result: The result of this research shows that the potential of the community health nurses roles in the area with high risk infection of the STD/HIV-AIDS in Banyumas Regency are: 1) doer